Effectively enhanced comprehensive electrical performance of ZnO varistors by a fast combinatorial refinement method. (October 2021) - Li, Zhuyun; Ren, Xin; Wang, Xin; You, Wanli; Zhong, Meilian; Kong, Anting; Lao, Xuebin; Jiang, Haibo; Yu, Wenqi; Jin, Lujiang; Yao, Zheng; Shi, Liyi
Abstract: We demonstrated a rapid refinement method consisting of ball milling and sand milling, which greatly improved the milling efficiency, the dispersion of the suspension and the electrical properties of the ZnO varistors. The effects of the refinement processes on the size of the doping additive oxides, the microstructure and the comprehensive electrical properties, especially the degradation behaviors of the ZnO varistors were investigated. Compared with the traditional single ball milling production mode, the additive refinement process combined 6 h ball milling with 15 min sand milling greatly improved the milling efficiency by 6.68 times, with better electrical properties that the leakage current decreased from 3.46 to 1.54 μA, the clamping voltage ratio decreased from 1.99 to 1.96, and the non-linear coefficient increased from 29.1 to 47.